PENGARUH KEPRIBADIAN DAN KECERDASAN EMOSIONALTERHADAP KINERJA KARYAWAN TRAVEL JUWITA LAMPUNG - JAKARTA - Defrizal Defrizal; Renta Ulina Sihombing (Jurnal Manajemen dan Bisnis, 2021)
The objectives of this study are as follows: (1) To analyze the influence of personality on the performance of Travel Employees of Juwita Lampung-Jakarta. (2) To analyze the influence of Emotional Intelligence on the Performance of Travel Employees of Juwita Lampung-Jakarta. (3) To analyze the influence of Personality and Emotional Intelligence on the Performance of Travel Employees of Juwita Lampung-Jakarta. The measuring instrument used in this research is a questionnaire. The population of this study were 30 employees of Travel Juwita Lampung-Jakarta. Based on the results of data analysis (1) Personality has a positive and significant influence on the Performance of Travel Employees of Juwita Lampung-Jakarta. (2) Emotional Intelligence has a positive and significant influence on the Performance of Travel Employees of Juwita Lampung-Jakarta. (3) Personality and Emotional Intelligence have a positive and significant effect together on the Performance of Travel Employees of Juwita Lampung-Jakarta Travel. In order to improve employee performance, Travel Juwita Lampung-Jakarta must pay attention to employees so that they can manage their own work plans properly so that they can maximize their work to be completed on time.